Differentiation of Trace Metal Contamination Level between Different Urban Functional Zones in Permafrost Affected Soils (the Example of Several Cities in the Yamal Region, Russian Arctic) - Timur Nizamutdinov; Eugenia Morgun; Alexandr Pechkin; Jakub Kostecki; Andrzej Greinert; Evgeny Abakumov (Minerals, 2021)
Dynamically developing urbanization causes a number of environmental effects, including those related to the chemical transformation of soils. Relatively less information about the urban areas of the Arctic and Subarctic zones, constructed mostly on permafrost and intensively populated areas can be found. By the example of the analysis of basic soil properties and concentrations of trace metals in the soils of the cities of Salekhard, Urengoy, Nadym, Novy Urengoy and Gaz Sale (the Yamalo-Nenets Autonomous District), as well as various functional zones within the cities, the relationship between the age of the cities, the level of anthropogenic pressure and the type of parent materials and the character of accumulation of metals in the soil profile of urban soils have been described. The direct correlation was found between the content of Pb, Cr, Ni, As and soil sorption characteristics. In young cities built on sandy sediments, there is less accumulation of heavy metals in the topsoil horizons. Relatively higher concentrations of Cu and Cd were noted in soils of industrialized cities, regardless of functional zones. The higher content of Cr, Ni, Cu, Zn, As and Pb has been registered in older zones also frequently used for residential purposes. The calculated values of the PI index for some functional zones of young cities show the medium and high content of heavy metals. The analysis of Igeo and PLI indices shows a large diversity both in relation to individual cities and their functional zones. Soil quality, in spite of the high level of anthropogenic load, was assessed as mostly satisfactory.